The Legal Construction of Mangrove Protection in Climate Change Mitigation: Legal Study on The South Sulawesi Scale - Amir, Irfan; Hamzah, Hamzah; Hasanuddin, Sultan (Faculty of Law, Universitas Pekalongan, 2024)
Mangroves are coastal ecosystems that play a vital role in protecting the environment and the economy, as well as aiding climate change mitigation. The mangrove rehabilitation program in South Sulawesi is a strategic step by the government to ensure the sustainability of coastal environments. The success of these efforts depends on the participation of all stakeholders. The aim of this research is to identify the impacts and implications of constitutional legal protection on the conservation, restoration, and management of mangrove ecosystems as part of climate change mitigation strategies in South Sulawesi. This research utilizes normative legal research methods with a focus on the legal framework related to Mangroves and Climate Change in South Sulawesi, exploring legal sources such as laws, regulations, and relevant legal documents, and applying document content analysis techniques and constitutional legal approaches to identify potential legal improvements in protecting mangroves and addressing climate change in the region. The research findings indicate that legal protection in South Sulawesi plays a crucial role in preserving and restoring the mangrove ecosystem and mitigating climate change. The enforcement of Law No. 32 of 2009 and local regulations provides a strong legal foundation for safeguarding the mangrove ecosystem through land permit restrictions and the establishment of conservation areas. Mangrove preservation policies are also applied at the national level with the support of Indonesia's FOLU Net Sink 2030 Operational Plan. South Sulawesi, through its regional mangrove working group, plays a key role in coordinating mangrove preservation efforts at the regional level. Furthermore, the role of the Indonesian President in the G20 Presidency underscores Indonesia's commitment to climate change mitigation, highlighting the preservation of the mangrove ecosystem as an example for other countries. With collaboration and community awareness, South Sulawesi has the potential to become a successful model in mangrove preservation and climate change mitigation, despite challenges such as economic issues, public awareness, and climate change